Pengaruh Perilaku Sikap Kerja terhadap Kinerja Pelayanan Karyawan di Asstro Highlands Ciater - Qurrota Ayun; Rusman Frendika; Firman Shakti Firdaus (UNISBA Press, 2023)
Abstract. Astro highlands ciater As a place to relax with family, colleagues or relatives, vacation activities, family time and business activities. offers culinary delights amidst the coolness of the tea gardens. Asstro Highlands Ciater in the form of work attitude behavior in the ability to socially relate to fellow employees has not gone well, there is a lack of respect for one another. Based on this phenomenon, the problems in this study are formulated as follows: (1) How is the work attitude of the employees at Astro Highlands Ciater? (2) How is the service performance of the employees at Astro Highlands Ciater? (3) How much influence does work attitude behavior have on employee service performance at Astro Highland Ciater?. This research uses descriptive and verification analysis methods and operates the calculations using the IBM SPSS Version 25.0 program. Respondents in this study were Asstro Highlands Ciater employees, totaling 73 people. The variables studied in this study are work attitude behavior (X) and employee service performance (Y). Data collection was carried out by field research (Field Research) and library research (Library Research). The results of this study conclude that: (1) Asstro Highlands Ciater Employee Service Attitude Behavior is included in the